(untitled) (Web of Teachers: Inderscience Research, 2025)
This article discusses the significant role of physical education in promoting youth health. It highlights how regular physical activity supports the physical, mental, and emotional well-being of young people. The paper emphasizes the importance of incorporating physical education into school curricula to develop healthy habits, reduce the risk of chronic diseases, and support psychological development.